Identification of forensically important fly eggs using a potassium permanganate staining technique - Sukontason K. (2014)
Fly eggs found in corpses can be utilized as entomological evidence in forensic investigations of deaths if the species of fly and the developmental rate at a temperature similar to the death scene are known. The species identification of fly eggs is particularly important, and previously, scanning electron microscope has been used for this purpose. Herein, we report a simple technique, using light microscopy, to identify forensically important eggs of Chrysomya rufifacies (Macquart), Chrysomya megacephala (Fabricius), Chrysomya pacifica Kurahashi, Chrysomya nigripes Aubertin, Aldrichina grahami (Aldrich), Lucilia cuprina (Wiedemann), Musca domestica L. and Megaselia scalaris (Loew). A 1% potassium permanganate solution was used to stain egg surfaces for 1 min, followed by dehydration in 15, 70, and 95%, absolute alcohol (each solution for 1 min) and the eggs were permanently mounted. The characteristics are based on the width of plastron, morphology of plastron area surrounding the micropyle and chorionic sculpturing, with the length of egg being used as supplemental feature. © 2004 Elsevier Ltd. All rights reserved.